Time-series analysis of trends in the incidence rates of successful and attempted suicides in Thailand in 2013–2019 and their predictors - Suwanna Arunpongpaisal; Sawitri Assanagkornchai; Virasakdi Chongsuvivatwong; Nattakorn Jampathong (BMC Psychiatry, 2022)
Abstract Background Suicide rates are of increasing concern worldwide. There are approximately 4000–5000 deaths by suicide each year in Thailand. This study examined trends in annual incidence rates and predictors of successful and attempted suicides in Thailand (2013–2019). Methods Secondary data analysis was conducted on data from two national-level databases: The National Health Security Office and the National Death Certification Registry System. Time-related trends and predictors of successful and attempted suicides were calculated using joinpoint regression and multivariable logistic regression analyses, respectively. Results Of all successful suicide cases from 2013 to 2019, about 80% involved men, with an average age of 45.37 (± 16.43) years. Predictors of successful suicide included male sex, older age, using highly lethal methods, and no prior psychiatric treatment. Among individuals admitted to hospitals following a suicide attempt from 2013– to 2019, the average age at first admission was 38.83 ± 22.47 years, with women more heavily represented than men. Only 2.3% of these patients received psychiatric treatment in the hospital. Predictors of attempted suicide included female sex; adolescent or adult; and mental, alcohol, or substance-related disorder(s). Age-standardized annual rates per 100,000 people showed that, through 2019, suicide incidence increased slightly, and attempts decreased. Conclusions There was a significantly increasing trend in successful suicide during the 7 years; the increase was more notable among men. The study highlights sex-related gaps in public health owing to an identified higher incidence of suicide among men, and a higher incidence of suicide attempts in women adolescents, emphasizing the need to consider sex-sensitive issues in individual as well as societal contexts.